2018
DOI: 10.1097/dcr.0000000000000934
|View full text |Cite
|
Sign up to set email alerts
|

Increased Postoperative Morbidity Associated With Prolonged Laparoscopic Colorectal Resections Is Not Increased by Resident Involvement

Abstract: Although longer operative times confer increased postoperative morbidity, there was no significant difference in complication rates within the highest tertile between cases with and without resident participation. Resident involvement does not appear to add to the risk of morbidity associated with longer and more complicated surgeries. See Video Abstract at http://links.lww.com/DCR/A440.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…The present results showed that prolonged OT is associated with an increased risk of postoperative noninfective complications, and not linked to infective complications, anastomotic complications, and hospital stay >5 days. These data are consistent with previous findings but direct comparisons between the studies are challenging because of the cutoff value to define a prolonged operation varied in each study as well as the characteristics of the patient samples analysed (including different types of colorectal procedures and different indications for surgery) [3, 6, 9, 34, 41]. In a large retrospective cohort study, Guidolin et al [9] observed that OT was linearly associated with any type of postoperative complication.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The present results showed that prolonged OT is associated with an increased risk of postoperative noninfective complications, and not linked to infective complications, anastomotic complications, and hospital stay >5 days. These data are consistent with previous findings but direct comparisons between the studies are challenging because of the cutoff value to define a prolonged operation varied in each study as well as the characteristics of the patient samples analysed (including different types of colorectal procedures and different indications for surgery) [3, 6, 9, 34, 41]. In a large retrospective cohort study, Guidolin et al [9] observed that OT was linearly associated with any type of postoperative complication.…”
Section: Discussionsupporting
confidence: 85%
“…because of the cutoff value to define a prolonged operation varied in each study as well as the characteristics of the patient samples analysed (including different types of colorectal procedures and different indications for surgery)[3,6, 9,34,41]. In a large retrospective cohort study,Guidolin et al [9] observed that OT was linearly associated with any type of postoperative complication.…”
mentioning
confidence: 99%
“…This is the first large-scale study comparing clinical characteristics and operative factors for major and minor complications of patients who underwent elective colonic resection for diverticulitis in the international multi-institutional setting. The postoperative major and minor outcomes have been described previously in various distinctive case series, such as infectious or complicated complications [15][16][17] . Until present, it has been unclear whether the severity of diverticulitis phenotype of patients or the effect of operative management has an impact either alone or combined among the major and minor complications for elective surgery internationally.…”
Section: Discussionmentioning
confidence: 84%
“…However, it requires mobilization of the cecum, which may be an excessive procedure if partial wedge resection by LECS is otherwise possible. A previous report showed that partial cecectomy, compared with the hemicolectomy, could preserve the ileocecal valve, reduce intraoperative blood loss and postoperative morbidity, and shorten postoperative hospital stay in cases with tumors around the cecum . LECS avoids unnecessary colectomy even if the tumor is close to the cecum.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that partial cecectomy, compared with the hemicolectomy, could preserve the ileocecal valve, reduce intraoperative blood loss and postoperative morbidity, and shorten postoperative hospital stay in cases with tumors around the cecum. 6 LECS avoids unnecessary colectomy even if the tumor is close to the cecum. Furthermore, ileocecal resection requires a small abdominal incision to pull out the specimen and reconstruct the digestive tract, but several complications have been reported, including incisional hernia, wound infection, and adhesion relating to the small abdominal incision.…”
Section: Discussionmentioning
confidence: 99%